Managing risk in pastoral systems: Research and outreach experiences of the Pastoral Risk Management (PARIMA) Project in southern Ethiopia and northern Kenya - Gebru, G.; Desta, S.; Coppock, D. Layne (Ethiopian Society of Animal Production, 2003)
In the context of East African pastoralism, improved risk management is proposed to offer ways to promote wealth conservation, reduce poverty, mitigate conflicts, and enhance food security at the household level. The Pastoral Risk Management (PARIMA) project is a multi-disciplinary, effort funded by USAID from 1997 to 2006. The two main components of the project include research arid outreach. The study area extends from Hagremariam in southern Ethiopia to Isiolo and Baringb Districts' in north-central Kenya. The study area represents an intact eco-marketing region, hosts 10 major ethnic groups, and is beset by pervasive poverty, violence, food insecurity, poor infrastructure, and inadequate public services: Research has focused on risk mapping, household survey, and community-level case studies to identify prominent risks for pastoralists, clarify pastoral coping strategies, and reveal possible Development interventions. Outreach disseminates research information among researchers, Development agents; policy makers, and communities. Outreach has also engaged in efforts to build awareness and capacity of pastoral communities and Development agents to implement risk-management interventions using pilot projects. Degree training has focused on master's and doctoral students, both in East Africa and the United States. Non-degree training includes workshops and interactive field tours for communities, Development facilitators, and policy makers. One Development vision of the PARIMA project is based on how to promote household wealth accumulation and conservation via asset and income diversification. The process could involve encouraging households to become involved in more timely livestock sales before crises occur, putting some revenue in draught-proof alternative investments, and then focusing on how to achieve a degree of sustainable livelihood diversification. This paper reviews some general findings and experiences from the PARIMA project over the period 1997 to 2002, with a focus on work conducted in southern Ethiopia.